Challenges in Trade Facilitation: The Case of the Designated Examination Area (DEA) in Davao - Mendoza, Ronald U (Archīum Ateneo, 2015)
Trade facilitation is defined as the simplification and harmonization of international trade procedures, referring to activities, practices, and formalities involved in collecting, presenting, communicating, and processing data required for the movement of goods in international trade.4 The need to provide information, submit declarations, and submit to border checks adds to business costs caused by associated time delays, which then lead to forgone business opportunities and reduced competitiveness. Thus, the aim is to maximize efficiency and reduce cost burdens associated with these trade processes, while safeguarding legitimate regulatory objectives. In order to help illustrate the challenges to upgrading the Bureau of Customs (BOC) to fulfill its trade facilitation mandate5, this case elaborates on the issues surrounding the operations of the designated examination area (DEA) in Davao.